Graph Transformation for Specification and Programming - Andries, Marc; Engels, Gregor; Habel, Annegret; Hoffmann, Berthold; Kreowski, Hans-Jörg; Kuske, Sabine; Plump, Detlef; Schürr, Andy; Taentzer, Gabriele (Science of Computer Programming)
The framework of graph transformation combines the potentials and advantages of both, graphs and rules, to a single computational paradigm. In this paper we present some recent developments in applying graph transformations as a rule-based framework for the specification and development of systems, languages, and tools. After reviewing the basic features of graph transformation, we discuss a selection of applications, including the evaluation of functional expressions, the specification of an interactive graphical tool, an example specification of abstract data types, and the definition of a visual database query language. The case studies indicate the need for suitable structuring principles which are independent of a particular graph transformation approach. To this end, we present the concept of a transformation unit, which allows systematic and structured specifications and programming based on graph transformation.

Handbook of Graph Grammars and Computing by Graph Transformation: Vol. 2: Applications, Languages, and Tools - Ehrig, Hartmut; Engels, Gregor; Kreowski, Hans Jörg; Rozenberg, Grzegorz
Graph grammars originated in the late 60s, motivated by considerations about pattern recognition and compiler construction. Since then, the list of areas which have interacted with the development of graph grammars has grown quite impressively. Besides the aforementioned areas, it includes software specification and development, VLSI layout schemes, database design, modeling of concurrent systems, massively parallel computer architectures, logic programming, computer animation, developmental biology, music composition, visual languages, and many others. The area of graph grammars and graph transformations generalizes formal language theory based on strings and the theory of term rewriting based on trees. As a matter of fact, within the area of graph grammars, graph transformation is considered as a fundamental computation paradigm where computation includes specification, programming, and implementation. Over the last three decades, graph grammars have developed at a steady pace into a theoretically attractive and important-for-applications research field. Volume 2 of the indispensable Handbook of Graph Grammars and Computing by Graph Transformations considers applications to functional languages, visual and object-oriented languages, software engineering, mechanical engineering, chemical process engineering, and images. It also presents implemented specification languages and tools, and structuring and modularization concepts for specification languages. The contributions have been written in a tutorial/survey style by the top experts in the corresponding areas. This volume is accompanied by a CD-Rom containing implementations of specification environments based on graph transformation systems, and tools whose implementation is based on the use of graph transformation systems.

A View-based Approach to System Modeling Based on Open Graph Transformation Systems - Heckel, Reiko; Engels, Gregor; Ehrig, Hartmut; Taentzer, Gabriele (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 2: Applications, Languages and Tools)
The idea of a combined reference model- and view-based specification approach has been proposed recently in the software engineering community. In this chapter we present a specification technique based on open graph transformation systems (in the double-pushout approach) by a new loose semantics for rule-based systems, which allows to model the interaction between different views, and by explicit frame conditions which restrict these interactions to an interface of open types. On this background, formal notions of view and view relation are developed and the behavior of views is described by the loose semantics. Based on the assumption that dependencies between different views are faithfully described by a common reference model, a construction is developed for the automatic integration of views. The views and the reference model are kept consistent manually, which is the task of a model manager. All concepts and results are illustrated at the well-known example of banking system.

Classification and Comparison of Module Concepts for Graph Transformation Systems - Heckel, Reiko; Engels, Gregor; Ehrig, Hartmut; Taentzer, Gabriele (Handbook of Graph Grammars and Computing by Graph Transformations, Volume 2: Applications, Languages and Tools)
In this chapter we use a three-level approach for analyzing module concepts for graph transformation systems. Based on the observation that module architectures consist of basic specications like body or export interface and relations like the implementation relation between them, or the import relation between a client and a server module, module concepts are characterized by answering the questions 1. What are the basic specifications? 2. Which relations between specifications are used? 3. How are specifications and relations combined to module architectures? These three questions are investigated for five module concepts available in the literature. As a reference example, a samplemodular specification of resource management in distributed operating systems is presented.

Kundenbindung aus Kundensicht: Konzeptualisierung, Operationalisierung, Verhaltenswirksamkeit

Depth profile of the implantation-enhanced intermixing of Ga+ focused ion beam in AlAs/GaAs quantum wells - Eshlaghi, Soheyla; Meier, Cedrik; Suter, Dieter; Reuter, D.; Wieck, A. D. (Journal of Applied Physics)

Realisierung fächer- und lernortübergreifender Ausbildungskonzepte - Kremer, H.-Hugo (Lehren und Lernen in der Aus- und Weiterbildung)

Lernfelder - Motor didaktischer Innovationen - Kremer, H.-Hugo; Sloane, Peter F. E. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Can students act? Explorative Studie zum Erfolg fächer- und lernortübergreifender Maßnahmen - Kremer, H.-Hugo (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Das virtuelle Seminar "Wirtschaftspädagogik Köln-München" - Kremer, H.-Hugo; Wilbers, K. (Virtus, virtuelle Universitätssysteme Köln: Jahresbericht 1998/1999)